2016
DOI: 10.1158/1078-0432.ccr-15-1506
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and Tumor Fn14 Expression as Determinants of Pharmacodynamics of the Anti-TWEAK Monoclonal Antibody RG7212 in Patients with Fn14-Positive Solid Tumors

Abstract: Purpose: The TWEAK-Fn14 pathway represents a novel anticancer target that is being actively investigated. Understanding the relationship between pharmacokinetics of anti-TWEAK therapeutics and tumor pharmacodynamics is critical. We investigated exposure-response relationships of RG7212, an anti-TWEAK mAb, in patients with Fn14-expressing tumors.Experimental Design: Patients with Fn14-positive tumors (IHC!1þ) treated in a phase I first-in-human study with ascending doses of RG7212 were the basis for this analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Lassen and colleagues have recently reported on a phase 1 study of RG7212, a monoclonal antibody targeting TWEAK, reporting good tolerability (no DLTs and no significant hepatopancreatic toxicities), expected pharmacodynamic changes, and some evidence of antitumor activity (16). RG7212 was shown to reduce tumor TWEAK-TweakR signaling in an exposure-dependent manner (17). To our knowledge, our study is the first phase 1 clinical trial of a humanized IgG1 antibody to TweakR.…”
Section: Discussionmentioning
confidence: 99%
“…Lassen and colleagues have recently reported on a phase 1 study of RG7212, a monoclonal antibody targeting TWEAK, reporting good tolerability (no DLTs and no significant hepatopancreatic toxicities), expected pharmacodynamic changes, and some evidence of antitumor activity (16). RG7212 was shown to reduce tumor TWEAK-TweakR signaling in an exposure-dependent manner (17). To our knowledge, our study is the first phase 1 clinical trial of a humanized IgG1 antibody to TweakR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that TWEAK/Fn14 signaling promotes invasion, migration, and survival in many types of cancer cells, including glioblastoma, neuroblastoma, and breast cancer cells[20-22]. One study demonstrated therapeutic benefits when using a TWEAK-blocking antibody for cancer therapy[23]. These reports indicated that TWEAK/Fn14 signaling relates to tumor progression and blocking the TWEAK/Fn14 pathway could be beneficial in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…22,28,90,91 RG7212, a neutralizing monoclonal antibody (mAb) targeting TWEAK, can inhibit TWEAK/Fn14 signaling and suppress the growth of solid tumors in patients. 33,34 In preclinical trials, RG7212 blocked TWEAK/Fn14 signaling, NF-κB activation, and cytokine secretion in cultured tumor cells and even inhibited tumor growth in murine models. 35 Phase I studies were conducted in recent years, showing that RG7212 possesses excellent tolerability and favorable pharmacokinetics as administered systemically.…”
Section: Tweak and Fn14 As Biomarkers And Therapeutic Targetsmentioning
confidence: 99%